Impact of ERP Implementation on Company Bottled Water to Performance Company - Pranoto Pranoto; Achmad Chaerul Muslim; Rudi Prasetya Timur (Jurnal Economia, 2023)
AbstractThis study evaluates the impact of implementing an Enterprise Resource Planning (ERP) system on the performance of CV Tirta Sasmita, a bottled drinking water producer. It addresses the challenge of fragmented business processes, hindering effectiveness and efficiency, along with suboptimal utilization of data resources. Qualitative methods, including interviews, observations, and document analysis, were employed. The study applied the ADDIE approach to tailor ERP systems to the company's needs and processes.The study yielded three significant findings. Firstly, researchers successfully developed a customized ERP system aligned with the company's requirements. Secondly, there was a tangible enhancement in CV Tirta Sasmita's financial performance, notably reflected in an increased total turnover asset ratio. Thirdly, employee performance exhibited improvements in work quantity, quality, punctuality, effectiveness, and independence.This research offers valuable insights for similar businesses or those considering ERP system implementation, highlighting its potential to enhance operational efficiency and performance.Keywords:Information System, AMDK, ERP, Company Performance, Total Turn Over Asset Ratio